2007
DOI: 10.1103/physrevb.76.174407
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of electronic structure and martensitic transition in epitaxialNi2MnGafilms

Abstract: We investigate the martensitic transition of single crystalline Ni 2 MnGa͑110͒ /Al 2 O 3 ͑1120͒ and Ni 2 MnGa͑100͒ /MgO͑100͒ films using magnetometry, x-ray diffraction, x-ray absorption spectroscopy, and x-ray magnetic circular dichroism. The martensitic transition from the cubic austenite phase to the low symmetry martensite phase depends strongly on the chosen substrate. For ͑110͒ oriented films on Al 2 O 3 , the martensitic phase is significantly more stable than for the ͑100͒ oriented films on MgO. A rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…In thin films of shape memory alloys with suitable sputtering parameters sharp transitions have also been observed, as reported for Ni-Mn-Ga thin films. 32 The M s in all the films were found to be above RT which is a good signature to use them for RT applications.…”
Section: A X-ray Diffraction Analysismentioning
confidence: 97%
“…In thin films of shape memory alloys with suitable sputtering parameters sharp transitions have also been observed, as reported for Ni-Mn-Ga thin films. 32 The M s in all the films were found to be above RT which is a good signature to use them for RT applications.…”
Section: A X-ray Diffraction Analysismentioning
confidence: 97%
“…Intense research currently focuses on the fabrication of epitaxial FSMA films. However, magnetically induced reorientation has been reported only in a few cases [7][8][9][10]. In order to achieve magneto-strain effects similar to bulk materials, free-standing films with improved crystallinity and microstructures are demanded.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate nature and its temperature during deposition are seemingly the main factors determining whether single crystalline or textured polycrystalline state of film is formed. It was found that Ni-Mn-Ga films deposited at room temperature on the alumina ceramic [4], Mo foil [2,3,9], MgO(100) [6] or Si(100) [7] wafers are polycrystalline and exhibit predominantly 220 fiber texture after subsequent heat-treatment at 1070K, whereas these films demonstrated an epitaxial growth during the deposition on heated single crystalline substrates such as Al 2 O 3 (11-20) [5], MgO(100) [5,8,12] or SrTiO 3 (100) [10]. The Ni-Mn-Ga/substrate thin film composites, where the substrate is a micrometer-sized thin metallic foil are promising materials for microactuator applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of Ni-Mn-Ga films depend very much on the substrate nature, surface roughness, film thickness and technological details of their production. The transformation behavior and magnetic characteristics of these films are controlled by crystallography, substructure and residual stress [1][2][3][4][5][6][7][8][9][10][11][12]. The substrate nature and its temperature during deposition are seemingly the main factors determining whether single crystalline or textured polycrystalline state of film is formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation